2021
DOI: 10.1302/1863-2548.15.200235
|View full text |Cite
|
Sign up to set email alerts
|

One and done? Outcomes from 3961 patients managed via a virtual fracture clinic pathway for paediatric fractures

Abstract: Purpose The aim of this paper is to describe our experience with a virtual fracture management pathway in the setting of a paediatric trauma service. Methods All patients referred to the virtual fracture clinic service from the Paediatric Emergency Department (PED) were prospectively collected. Outcome data of interest (patients discharged, referred for urgent operative treatment, referred back to emergency department for further evaluation, referred for face-to-face clinical assessment and all patients who re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Five of the studies reported on the time between initial presentation and review in the VFC and all of these were within 72 h, indicating high compliance with the BOAST 7 guidelines ( 25 , 27 – 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five of the studies reported on the time between initial presentation and review in the VFC and all of these were within 72 h, indicating high compliance with the BOAST 7 guidelines ( 25 , 27 – 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported on outcomes after the VFC. The rate of direct discharge from VFC without the need for a further appointment ranged from 70% to 75% ( 27 29 ). This resulted in the saving of the following number of F2F fracture clinic appointments: 78/104 ( 28 ), 2,770/3,961 ( 27 ) and 33/44 ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In some trusts, common fracture patterns such as undisplaced radial head/neck fractures are deemed suitable for direct discharge from VFC with advice leaflets on expected recovery. The VFC pathway is mostly successful, with an infrequent need for unplanned face-to-face consultation and low reported late surgical intervention rates of 0.1–1% [ 3 , 4 ]. However, we contend that in the case of high-energy trauma, even where there is minimal radiographic fracture displacement, there should be a low threshold for referral to the on-call orthopaedic team or facilitation of face-to-face fracture clinic review to avoid missing concomitant injury.…”
Section: Discussionmentioning
confidence: 99%